Integrated research strategies for reproductive and developmental toxicology of real-world exposure: Integrating population epidemiology with in vivo and in vitro experiments - Cheng Qianhui; Li Sainan; Wang Linlin (生物医学转化)
Humans are continuously exposed to large numbers of complex chemical mixtures at low doses in real-world environments, which may pose potential threats to health, particularly to reproductive and developmental health. Therefore, understanding real-world exposure—specifically, the effects of chemical mixtures at environmental concentrations on health and their underlying mechanisms—is crucial. This requires integrating population epidemiological data with in vivo and in vitro toxicological studies to establish an integrated research framework for assessing the health effects of real-world exposure to chemical mixtures at environmental concentrations. This review systematically examines recent advancements in evaluating the health effects of real-world chemical exposure, with a particular focus on methodologies for identifying and characterizing chemical mixtures suitable for in vivo and in vitro toxicological experiments. Additionally, it reviews the application of these strategies in reproductive and developmental toxicology research. These studies lay the foundation for refining an integrated research framework for real-world exposure health effects and provide scientific evidence for more precise reproductive and developmental health risk assessment and intervention strategies.